La multimodalità del processo di astrazione in Marx nella relazione fra logica formale e dialettica - Lutero, Giancarlo (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
This essay discusses the significance and complexity of the notion of real abstraction as a necessary moment of the dialectical process, established by Karl Marx in the mature phase of his studies on the capitalistic mode of production. Often formal logic and dialectical science are contemplated as antithetical approaches. The conflictual relation between these two expressions of thought is problematic: the aforementioned logics could be regarded as two different expression of the same cognitive discourse, where dialectical science constitutes an “Aufhebung” of formal logic because it poses the need of the contradiction. An introduction presents the general framework and objectives of the work, briefly discussing the ideological role of scientism in capitalistic society and the centrality of conceptualization in knowledge, criticizing all those superficial expressions of neo-empiricism that despise any type of metaphysics (§ 1). The problem of the relationship between a logical-formal system and dialectical logic will be discussed, examining the relationships that exist between mathematical formalism, the axiomatic method, and indeterminate abstractions, opposed to a dialectical vision of reality (§ 2). The distorted use of formal and mathematical logic and the limits of axiomatic method, in relation to dominant economic science paradigm, is treated (§ 3). The relevance of real or determined abstraction in marxian investigation is discussed, in that particular organic totality which is the capitalistic mode of production (§ 4). At last, a discussion around the role of real abstraction in Das Kapital is proposed, deepening the features of specifically marxian dialectic and the correlated method of analysis (§ 5). The § 6 summarizes and closes the work. Real abstraction, Scientism, Neo-empiricism, Axiomatic method, Formal logic, Dialectic science, Economic methodology, Abstract-Concrete dynamic.